Resveratrol Attenuates Hyperoxia Lung Injury in Neonatal Rats by Activating SIRT1/PGC-1α Signaling Pathway - Yang, Kun; Yang, Menghan; Shen, Yunchuan; Kang, Lan; Zhu, Xiaodan; Dong, Wenbin; Lei, Xiaoping (American Journal of Perinatology, 2022)
Objectives Our previous study showed that resveratrol (Res) attenuates apoptosis and mitochondrial dysfunction in alveolar epithelial cell injury induced by hyperoxia by activating the SIRT1/PGC-1α signaling pathway. In the present study, we investigated whether Res protects against hyperoxia-induced lung injury in neonatal rats by activating SIRT1/PGC-1α signaling pathway.Methods Naturally delivered neonatal rats were randomly divided into six groups: normoxia + normal saline, normoxia + dimethyl sulfoxide (DMSO), normoxia + Res, hyperoxia + normal saline, hyperoxia + DMSO, and hyperoxia + Res. Lung tissue samples were collected on postnatal days 1, 7, and 14. Hematoxylin and eosin staining was used to evaluate lung development. Dual-immunofluorescence staining, real-time polymerase chain reaction, and western blotting were used to evaluate the levels of silencing information regulator 2-related enzyme 1 (SIRT1), peroxisome proliferator-activated receptor γ co-activator 1α (PGC-1α), nuclear respiratory factor 1 (Nrf1), Nrf2, transcription factor A (TFAM) and citrate synthase, the number of mitochondrial DNA (mtDNA) and mitochondria, the integrity of mtDNA, and the expression of TFAM in mitochondria.Results We found that hyperoxia insulted lung development, whereas Res attenuated the hyperoxia lung injury. Res significantly upregulated the levels of SIRT1, PGC-1α, Nrf1, Nrf2, TFAM, and citrate synthase; promoted TFAM expression in the mitochondria; and increased the copy number of ND1 and the ratio of ND4/ND1.Conclusion Our data suggest that Res attenuates hyperoxia-induced lung injury in neonatal rats, and this was achieved, in part, by activating the SIRT1/PGC-1α signaling pathway to promote mitochondrial biogenesis.Key Points
Keywords: bronchopulmonary dysplasia; resveratrol; SIRT1; PGC-1α; mitochondrial biogenesis